Gender relations and witches among the indigenous communities of Jharkhand, India - Mullick, S.B. (2000)
Indigenous societies in India are showing an increasing tendency towards growing inequality in gender relations. This is more pronounced in societies that have integrated with mainstream Indian society. The objective of this paper is to determine if there is any co-relation between the growth of unequal gender relations and the widespread belief and practice of condemnation of women witches, particularly among the Munda and the Ho in Jharkhand in India. Through an analysis and interpretation of myths, legends and witch songs, the paper endeavours to see the belief in which craft in the context of the changing socio-economic condition of the indigenous peoples of India. The belief in witches and the targeting of women as witches are only the external manifestations of a deep-rooted gender struggle as patriarchy in the dominant Hindu society influences indigenous cultures.